Dynamics of house state consolidation in Lima Metropolitan area: a cellular automata approach - MURAKAMI, Akinobu; GUILLEN, Victor PENA (Journal of The Japanese Institute of Landscape Architecture, 2017)
House consolidation is the progressive structural improvement of a house. The aim of this paper is to identify, describe and simulate the process of house consolidation. Houses located in informally developed blocks in Lima metropolitan area, are hypothesized to upgrade its state according to a local mechanism of perceived influence. A specifically designed Cellular Automata model based on actual data at the micro-scale of the block permits to track state transition process. An updating algorithm is devised to reproduce house consolidation process under experimental conditions where the access to this dynamic system is limited to only the construction state variable. A study area composed by three subdivided agricultural parcels has been used to characterize state transition process. Simulation allows to understand how the general model fits to different combinations of block size, composition and configurations observed in the empirical data. Limitations of this approach are rooted on the use of the single variable of state to replicate the whole spatial configuration and temporal trajectories. However, this study permits us to describe this complex system at the scale of the house, and to have access to the necessary information to replicate consolidation process, presenting a novel approach for studying the dynamics of informal urbanization from the bottom-up.